2000
DOI: 10.1046/j.1365-8711.2000.03542.x
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated monitoring of the eccentric O-star binary Iota Orionis: optical spectroscopy and photometry

Abstract: With the objective of investigating the wind–wind collision phenomenon and supporting contemporaneous X‐ray observations, we have organized a large‐scale, coordinated optical monitoring campaign of the massive, highly eccentric O9 III+B1 III binary Iota Orionis. Successfully separating the spectra of the components, we refine the orbital elements and confirm the rapid apsidal motion in the system. We also see strong interaction between the components during periastron passage and detect phase‐locked variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 37 publications
4
27
0
1
Order By: Relevance
“…At first sight, this is somewhat reminiscent of the case of ι Ori . ASCA observations of ι Ori (O9 III + B1 III, e = 0.764, Marchenko et al 2000) failed to reveal the expected variability between the periastron and apastron phases. However, in the case of HD 93403, we do observe a phase-dependence of the observed X-ray flux.…”
Section: Discussionmentioning
confidence: 95%
“…At first sight, this is somewhat reminiscent of the case of ι Ori . ASCA observations of ι Ori (O9 III + B1 III, e = 0.764, Marchenko et al 2000) failed to reveal the expected variability between the periastron and apastron phases. However, in the case of HD 93403, we do observe a phase-dependence of the observed X-ray flux.…”
Section: Discussionmentioning
confidence: 95%
“…These authors also found no evidence of any systematic profile deviations which are associated with non-radial pulsations. The latest optical monitoring (Marchenko et al 2000) again obtained data consistent with a proximity effect.…”
mentioning
confidence: 59%
“…It also emphasizes the poor phase sampling and serves as a useful highlight as to one of the reasons why the latest ASCA data presented in this paper were obtained. In column 3 we list the orbital phase at the time of observation, calculated from the ephemeris HJD periastron 2451 121X658 1 29X133 76E derived from the latest optical monitoring of this system (Marchenko et al 2000). As a result of the large number of orbits which have elapsed, the listed phases are only approximate and do not account for the apsidal motion detected in Iota Orionis (Stickland et al 1987;Marchenko et al 2000).…”
Section: P R E V I O U S X -R Ay O B S E Rvat I O N S O F I O Ta O R mentioning
confidence: 99%
See 2 more Smart Citations